(untitled) (Research, Society and Development, 2023)
In view of the high accident rate in the curved section located on the highway BR 101, Km 448 - Bahia, popularly known as the “priest’s curve”, the present study aimed to diagnose the geometric characteristics through AutoCad Civil 3D software and to verify the safety performance of the segment based on the analysis of traffic accident data, for the last six years, on this curve located in the city of Aurelino Leal. By means of the obtained results, it was possible to conclude that the stretch was a critical segment and high inconsistencies were found on the geometric design of the stretch of the federal highway (superelevation, track width, maximum grade and stopping sight distance) which combined were directly related to its low safety performance.